Maternal and fetal risk factors affecting perinatal mortality in early and late fetal growth restriction - Oya Demirci; Selçuk Selçuk; Pınar Kumru; Mehmet Reşit Asoğlu; Didar Mahmutoğlu; Barış Boza; Gürcan Türkyılmaz; Zafer Bütün; Resul Arısoy; Bülent Tandoğan (Elsevier, 2015)
Objective: To determine the factors which affect the perinatal deaths in early and late fetal growth restriction (FGR) fetuses using threshold of estimated fetal weight (EFW) < 5th percentile. Materials and Methods: This retrospective study included singleton 271 FGR fetuses, defined as an EFW < 5th percentile. All fetuses considered as growth restrictions were confirmed by birth weight. Fetuses with multiple pregnancy, congenital malformation, chromosomal abnormality, and premature rupture of membrane were excluded. Samples were grouped in early and late FGR. Early FGR fetuses was classified as gestational age at birth ≤ 34 weeks and late FGR was classified as gestational age at birth > 34 weeks. Factors which affect the perinatal deaths were analyzed descriptively in early and late FGR. The perinatal mortality was calculated by adding the number of stillbirths and neonatal deaths. Results: The study included 86 early and 185 late FGR fetuses, 31 resulted in perinatal deaths, 28 perinatal deaths were in early FGR, and three perinatal deaths were in late FGR. Perinatal deaths occurred more commonly in early FGR fetuses with an EFW < 3rd percentile. Prior stillbirth, preeclampsia, the degree of increasing vascular impedance of umbilical artery(UA) and uterine artery (UtA) showed significant correlation with perinatal death in early FGR. All three perinatal deaths in late FGR occurred in fetuses with EFW < 3rd percentile and severe oligohydramnios. Also, placental abruption and perinatal death was found significantly higher in increased vascular impedance of UtAs whatever the umbilical artery Doppler. Conclusion: Only EFW < 3rd percentile and severe olgohydramnios seem to be contributing factors affecting perinatal death in late FGR in comparison with early FGR.